Toxicity Testing Of White Pomegranate (Punica granatum L.) Fruit Extracts Using Brine Shrimp Lethality Test Method As A Candidate Of Anti-Cancer Drug - Firnanda, Ferian; Herupradoto, Eduardus Bimo Aksono; Rahmawati, Kadek; Kurnijasanti, Rochmah; Sukmanadi, Mohammad; Hidajati, Nove (Universitas Airlangga, 2021)
This research aimed to determine the effects of toxic white pomegranate fruit extract (Punica granatum L) against larvae of brine shrimp (Artemia salina Leach) indicated LC50 values below 1000 µg/ml. This study is purely experimental by using Brine Shrimp Lethality Test (BSLT). The study was divided into seven groups, namely ethanol extract of white pomegranate fruit (Punica granatum L) with a concentration of 31,25; 62,5; 125; 250; 500; 1000 µg/ml and negative control (seawater). Mortality data percentage of Artemia salina Leach analyzed by probit analysis. Results showed that the extract of white pomegranate fruit extract (Punica Granatum L) has a toxic effect with LC50 values of 248,6 µg/ml calculate from probit analysis. From these results, it can conclude that white pomegranate extract is toxic to larval shrimp (Artemia salina Leach) with Brine Shrimp Lethality Test (BSLT) method which means white pomegranate extract has the potential to be an anticancer drug.